A sudy of blood lactate profiles across different swim strokes - Kelly, M.; Gibney, G.; Mullins, J.; Ward, T.; Donne, B.; O'Brien, M. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
Freestyle swims of varying frequency and intensity are recommended for the determination of specific training programmes for competitive swimmers. This study compared lactate and heart rate responses to swims of the same relative intensity in all four basic swimming strokes. Eleven swimmers (five females, six males) took part in the study. Individual speeds, blood lactates and heart rates were monitored during 4 x 200 m swims performed at four different intensities between 80% and maximum in each of the four basic strokes and in the medley. Multiple correlation analysis showed the existence of significant correlation between speeds at the onset of blood lactate accumulation for all strokes (P < 0.01). Significant correlations were also found for maximum speeds across strokes (P < 0.01). The interstroke speed conversion ratio was constant at both the onset of blood lactate accumulation and maximum effort in all strokes. Lactate levels were more variable across strokes at different swimming intensities. Heart rates also showed great variability. The results of this study show that the most significant stroke correlations are found using speed rather than lactate or heart rate comparisons.